Structural geometry, electronic structure, thermo-electronic and optical properties of GaCuO2 and GaCu0.94Fe0.06O2: a first principle approach of three DFT functionals. Issue 17 (22nd November 2021) - Howlader, Debashis; Hossain, Md. Sayed; Chakma, Unesco; Kumer, Ajoy; Islam, Mohammad Jahidul; Islam, Md. Tawhidul; Hossain, Tomal; Islam, Jahedul
ABSTRACT: As Gallium oxides have been using in optoelectronic devices due to its high potentiality and efficiency, therefore, the Gallium–Copper oxide crystal has been computationally designed and screened for its electronic structure, thermo-electronic and optical properties using density functional theory (DFT). To kick off, GGA) with PBE has been implemented for the crucial screening of its structural geometry and the optimisation for both GaCuO2 and GaCu0.94 Fe0.06 O2 . Afterwards, the electronic structure, thermo-electronic and optical properties were analysed from optimised structures. In addition, for the comparison study of obtained data of the GGA with PBE functional with two DFT functionals, such as LDA with CA-PZ and GGA with RPBE methods have been performed. The band gaps for GaCuO2 are 0.756, 0.786 and 0.759 eV for the GGA with PBE, GGA with RPBE, and LDA with CA-PZ, respectively, whereas it has garnered after 6% Fe doping (GaCu0.94 Fe0.06 O2 ) is at 0.00 eV. And come to think of it, the thermo-electronic and thermophysical properties have been added to endow with the absorption of visible light, thermal stability and thermal state before and after doping which leads to use these crystals in lasers, solar cell even luminescent as optoelectronic materials.